Реальный элементный состав и термостойкость детонационной алмазосодержащей шихты - Долматов, В.Ю.; Юрьев, Г.С.; Веретенникова, М.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The work is devoted to the research of a real elemental composition of detonation diamondcontaining blend (DB) obtained in different conditions by different producers, as well as its thermal stability in the air atmosphere. Focus was on the study of DB obtained by new detonation synthesis methods – in aqueous solution of a reducing agent.